The Conception and Role of the Student Support Network of the Federal Institute Farroupilha - São Vicente do Sul Campus (Research, Society and Development, 2019)
The article aims to present an analysis of the conceptions of the members of the Student Support Network about the demands presented by the students and the organization of the work with the Farroupilha Federal Institute – São Vicente do Sul Campus (IFFar-SVS). For this, we opted for the qualitative approach through field and documentary research. Field research was done by sampling among IFFar-SVS professionals who are part of the Network, and data collection was carried out in 2017 through semi-structured interviews. In documentary research, IFFar-SVS's institutional documents were used. After analyzing the data, it was realized that the professionals understand that in face of the complexity that involves the demands, the integrated work achieves a greater effectiveness in the mediation or resolution of the situations and in this way contributes to the learning process of the students. Therefore, it is believed that the main contribution of the study was to highlight, through interviews analysis, the meaning of interdisciplinary work as an exchange and cooperation of knowledge to understand and carry out actions that promote important resolutions to the needs of students as subjects of their story.